Peace-building in the Minds of Early Childhood Education Teachers: Voices from Pakistan - Seema Lasi, Jennifer Jag Jiwan, Zahida Batool, Salima Dhanani, Kishore Shrestha (JECCE, 2023)
Peace-building initiatives from early years of life result in preventing violence in homes, schools and communities and plays a vital role in ensuring social cohesion, creating peaceful societies and promoting sustainable economic and social development. Against this background, Asia Pacific Regional Network for Early Childhood (ARNEC) conducted a research study to explore what is in the minds of teachers regarding peace and peace-building. The study followed a qualitative research design, respondents were selected conveniently to conduct in-depth interviews. Teachers specified a wide range of description on meaning of peace including positive and negative peace.